Increasing Javanese Vocabulary Through Dolanan Lir Ilir Songs as a Form of Local Wisdom in Group B Children - Suhratun, Rohman (JURNAL PENA PAUD, 2024)
This study analyzes the effectiveness of implementing the traditional song “Lir-Ilir” in improving the mastery of Javanese vocabulary in group B learners of Tunas Kusuma Kindergarten Malang. Using a mixed method approach with a classroom action research design, this study involved 15 learners consisting of 6 boys and nine girls. Data was collected through structured observation, in-depth interviews, field notes, and documentation. The research was conducted in two learning cycles. The results showed a significant increase from the initial condition of 20% to 73.33% in cycle I and 86.66% in cycle II, with a total increase of 66.66%. Evaluation of the ability to associate visual representations with vocabulary reached an optimal result of 100% at the second meeting in both cycles. The results indicate that using the song “Lir-Ilir” effectively improves the mastery of Javanese vocabulary while preserving local wisdom